Mohammad Taufiq PERSEPSI MAHASISWA AKUNTANSI DAN AKUNTAN PENDIDIK TERHADAP KODEETIK AKUNTAN : Program Studi Akuntansi, Universitas Nahdlatul Ulama Sidoarjo *email: cakufik@gmail.com - Mohammad Taufiq (Universitas Nahdlatul Ulama Sidoarjo, 2019)
This research was conducted to find out and compare perceptions of the public accountant code of ethics between students and educator accountants in the Nahdlatul Ulama University in Sidoarjo. Research data obtained from the distribution of questionnaires with research subjects and research objectives and obtained from the adoption and study of literature including from previous studies related to the writing of this study. Measurement of the results of the questionnaire was carried out with a Likert scale with data analysis techniques carried out to answer the problem formulation, namely: (1) using the data normality test, (2) the classic assumption test and (3) the hypothesis test that was accompanied by steps in decision making results research. Data analysis instruments using independent sample t-test. The analytical tool used to analyze is ANOVA (Analysis of Variance), From the data acquisition, the results of the analysis using the data analysis techniques above show that there are differences in perceptions between students and educator accountants towards the accountant's code of ethics. In general, the perception of accountants educators is better than the perceptions of accounting students.